LEGAL PROTECTION FOR CONSUMERS OF SHARIA FINTECH LENDING (PINJOL SYARIAH) IN INDONESIA: A REGULATORY AND ETHICAL REVIEW - Emmi Rahmiwita Nasution; Michael Turner; Elvis Ewane (Sharia Oikonomia Law Journal, 2025)
The rapid expansion of Sharia-compliant Financial Technology (Fintech) lending in Indonesia offers significant opportunities for financial inclusion. However, this growth has outpaced the development of a comprehensive regulatory framework, exposing consumers to considerable risks, including data privacy breaches, unclear contract terms, and unethical debt collection practices that may contravene Islamic principles. This study aims to critically analyze the adequacy of the current legal framework in providing protection for consumers of Sharia Fintech lending services in Indonesia, identifying key regulatory gaps and ethical inconsistencies. This research utilizes a normative juridical method. It involves a systematic analysis of primary legal sources, including laws and regulations from Indonesia’s Financial Services Authority (OJK), alongside secondary sources like academic literature and relevant case law. The analysis is further enriched by an ethical review based on foundational principles of Islamic law (Sharia). The findings reveal significant deficiencies in the existing legal infrastructure. While OJK regulations are in place, critical gaps persist concerning personal data protection, the transparency of digital contracts (akad), and effective dispute resolution mechanisms. Several prevalent industry practices, particularly in debt collection, were found to be misaligned with Sharia principles of justice (al-’adl) and the prohibition of harm (dharar). Legal protection for consumers in Indonesia’s Sharia Fintech lending sector is currently insufficient. Urgent regulatory reforms are necessary to strengthen data privacy laws, enforce transparent and fair contracts, and ensure that all operational practices strictly adhere to Sharia ethics to build a sustainable and trustworthy digital Islamic economy.